Geotechnical characterisation and design processes for anisotropic rock masses in open pits : a case study of an iron ore deposit in orientation biased anisotropic host rocks - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2018.